Sulfated carboxymethyl cellulose and carboxymethyl κ-carrageenan immobilization on 3D-printed poly-ε-caprolactone scaffolds differentially promote pre-osteoblast proliferation and osteogenic activity - Abbasi-Ravasjani, Sonia; Seddiqi, Hadi; Moghaddaszadeh, Ali; Ghiasvand, Mohammad-Ehsan; Jin, Jianfeng; Oliaei, Erfan; Bacabac, Rommel Gaud; Klein-Nulend, Jenneke (Frontiers in Bioengineering and Biotechnology, 2022)
The lack of bioactivity in three-dimensional (3D)-printing of poly-є-caprolactone (PCL) scaffolds limits cell-material interactions in bone tissue engineering. This constraint can be overcome by surface-functionalization using glycosaminoglycan-like anionic polysaccharides, e.g., carboxymethyl cellulose (CMC), a plant-based carboxymethylated, unsulfated polysaccharide, and κ-carrageenan, a seaweed-derived sulfated, non-carboxymethylated polysaccharide. The sulfation of CMC and carboxymethylation of κ-carrageenan critically improve their bioactivity. However, whether sulfated carboxymethyl cellulose (SCMC) and carboxymethyl κ-carrageenan (CM-κ-Car) affect the osteogenic differentiation potential of pre-osteoblasts on 3D-scaffolds is still unknown. Here, we aimed to assess the effects of surface-functionalization by SCMC or CM-κ-Car on the physicochemical and mechanical properties of 3D-printed PCL scaffolds, as well as the osteogenic response of pre-osteoblasts. MC3T3-E1 pre-osteoblasts were seeded on 3D-printed PCL scaffolds that were functionalized by CM-κ-Car (PCL/CM-κ-Car) or SCMC (PCL/SCMC), cultured up to 28 days. The scaffolds’ physicochemical and mechanical properties and pre-osteoblast function were assessed experimentally and by finite element (FE) modeling. We found that the surface-functionalization by SCMC and CM-κ-Car did not change the scaffold geometry and structure but decreased the elastic modulus. Furthermore, the scaffold surface roughness and hardness increased and the scaffold became more hydrophilic. The FE modeling results implied resilience up to 2% compression strain, which was below the yield stress for all scaffolds. Surface-functionalization by SCMC decreased Runx2 and Dmp1 expression, while surface-functionalization by CM-κ-Car increased Cox2 expression at day 1. Surface-functionalization by SCMC most strongly enhanced pre-osteoblast proliferation and collagen production, while CM-κ-Car most significantly increased alkaline phosphatase activity and mineralization after 28 days. In conclusion, surface-functionalization by SCMC or CM-κ-Car of 3D-printed PCL-scaffolds enhanced pre-osteoblast proliferation and osteogenic activity, likely due to increased surface roughness and hydrophilicity. Surface-functionalization by SCMC most strongly enhanced cell proliferation, while CM-κ-Car most significantly promoted osteogenic activity, suggesting that surface-functionalization by CM-κ-Car may be more promising, especially in the short-term, for in vivo bone formation.